Patients Undergoing Orthotopic Liver Transplantation Require Lower Concentrations of the Volatile Anesthetic Sevoflurane. (September 2017) - Baron-Stefaniak, Joanna; Götz, Viola; Allhutter, Andreas; Schiefer, Judith; Hamp, Thomas; Faybik, Peter; Berlakovich, Gabriela; Baron, David M.; Plöchl, Walter
Abstract : BACKGROUND: Sevoflurane is a volatile anesthetic commonly used to maintain anesthesia in patients with end-stage liver disease (ESLD) undergoing orthotopic liver transplantation (OLT). Growing evidence suggests that patients with ESLD have decreased anesthetic requirements compared to patients with preserved liver function. The potency of volatile anesthetics is expressed as the minimum alveolar concentration (MAC). In this prospective, blinded study, we compared the MAC of sevoflurane among patients with ESLD undergoing OLT and patients with normal liver function undergoing major abdominal surgery. METHODS: After propofol-induced anesthesia, the MAC of sevoflurane was assessed by evaluating motor response to initial skin incision in patients undergoing OLT and in patients with normal liver function undergoing major abdominal surgery. The MAC was determined using Dixon "up-and-down" method and compared between groups. In addition, the bispectral index was documented immediately before and after skin incision. RESULTS: Twenty patients undergoing OLT and 20 control patients were included in the study. The MAC of sevoflurane in patients undergoing OLT was 1.3% (95% confidence interval [CI], 1.1–1.4). In comparison, the MAC of sevoflurane in patients with normal liver function was 1.7% (95% CI, 1.6–1.9), equal to a relative reduction of the MAC in patients with ESLD of 26% (95% CI, 14–39). The bispectral index was higher in patients with ESLD than in control patients at 3 minutes before (47 [95% CI, 40–53] vs 35 [95% CI, 31–40], P = .011), 1 minute before (48 [95% CI, 42–54] vs 37 [95% CI, 33–43], P = .03), and 1 minute after skin incision (57 [95% CI, 50–64] vs 41 [95% CI, 36–47], P < .001). CONCLUSIONS: Our results suggest that the MAC of sevoflurane is lower in patients with ESLD than in patients with normal liver function after propofol-induced anesthesia. However, as we did not measure propofol concentrations at the time of skin incision, the difference in MAC should be interpreted with caution given that residual propofol may have been present at the time of skin incision. Abstract : Published ahead of print July 1, 2017.